2008
DOI: 10.1159/000134928
|View full text |Cite
|
Sign up to set email alerts
|

Very-High-Frequency Ultrasound Corneal Imaging as a New Tool for Early Diagnosis of Ocular Surface Toxicity in Rabbits Treated with a Preserved Glaucoma Drug

Abstract: Aim: To evaluate very-high-frequency (VHF) ultrasound imaging as a new method to detect and quantify early corneal epithelium changes induced by chronic exposure to a benzalkonium-chloride-containing antiglaucoma drug. Methods: Timolol preserved with 0.01% benzalkonium chloride solution was applied b.i.d. in 1 eye of 10 rabbits for 56 days. Unpreserved timolol solution was used as control. Ocular surface changes were assessed weekly combining clinical examinations, in vivo 60-MHz ultrasound imaging and ex vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 86 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…The central corneal thickness of 354 mm measured by CLSM agrees well with measurements obtained by very highfrequency ultrasound 20 and optical coherence tomography. 21 Although significant thickening was observed 3 days after cross-linking, corneal thickness had returned to normal values 1 week after treatment.…”
Section: Central Corneal Thickness and Stromal And Endothelial Cell Dsupporting
confidence: 82%
“…The central corneal thickness of 354 mm measured by CLSM agrees well with measurements obtained by very highfrequency ultrasound 20 and optical coherence tomography. 21 Although significant thickening was observed 3 days after cross-linking, corneal thickness had returned to normal values 1 week after treatment.…”
Section: Central Corneal Thickness and Stromal And Endothelial Cell Dsupporting
confidence: 82%
“…These experimental systems provide an excellent means for the objective comparison of the potential for cornea injury among several ophthalmic solutions; however, the extent to which these experimental models reflect the condition of the eyes in vivo remains unclear (Denoyer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…7,16,17 These experimental systems provide an excellent means of objectively comparing the potential for corneal injury among several ophthalmic solutions; however, the extent to which these experimental models reflect the condition of the eyes in vivo remains unclear. 18 Only a few in vivo studies of corneal electrical properties have been reported, [19][20][21] due to the difficulty of performing such analyses. Recent approaches to performing in vivo measurements have adapted the existing TER measurement methods for use in living animals.…”
Section: Introduction Introductionmentioning
confidence: 99%